1999
DOI: 10.1002/hep.510300311
|View full text |Cite
|
Sign up to set email alerts
|

L -Ornithine- L -aspartate lowers plasma and cerebrospinal fluid ammonia and prevents brain edema in rats with acute liver failure

Abstract: Brain edema sufficient to cause intracranial hypertension and brain herniation remains a major cause of mortality in acute liver failure (ALF). Studies in experimental animal models of ALF suggest a role for ammonia in the pathogenesis of both encephalopathy and brain edema in this condition. As part of a series of studies to evaluate the therapeutic efficacy of ammonia-lowering agents, groups of rats with ALF caused by hepatic devascularization were treated with L-ornithine-L-aspartate (OA), an agent shown pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(86 citation statements)
references
References 27 publications
6
77
0
3
Order By: Relevance
“…Similar results have been described in vitro following the exposure of cultured astrocytes to ammonia (Norenberg et al, 1991). Furthermore, prevention of brain edema in rats with ALF has been shown with ammonia-lowering strategies (Cordoba et al, 1999;Rose et al, 1999Rose et al, , 2000. Unrelated to ammonia, swelling-induced glutamate release was demonstrated in cortical astrocytes exposed to a hypo-osmotic medium (Kimelberg et al, 1990).…”
Section: Calcium-independent Glutamate Releasesupporting
confidence: 78%
See 2 more Smart Citations
“…Similar results have been described in vitro following the exposure of cultured astrocytes to ammonia (Norenberg et al, 1991). Furthermore, prevention of brain edema in rats with ALF has been shown with ammonia-lowering strategies (Cordoba et al, 1999;Rose et al, 1999Rose et al, , 2000. Unrelated to ammonia, swelling-induced glutamate release was demonstrated in cortical astrocytes exposed to a hypo-osmotic medium (Kimelberg et al, 1990).…”
Section: Calcium-independent Glutamate Releasesupporting
confidence: 78%
“…It has been suggested that ammonia plays an important role in the pathogenesis of brain edema (astrocytic swelling) in ALF. Increased brain water content has been described in both normal (Takahashi et al, 1991) and in portacaval shunted (Blei et al, 1994) rats infused with ammonia as well as in rats with liver devascularization (Rose et al, 1999). Similar results have been described in vitro following the exposure of cultured astrocytes to ammonia (Norenberg et al, 1991).…”
Section: Calcium-independent Glutamate Releasesupporting
confidence: 64%
See 1 more Smart Citation
“…49 In rat model of acute liver failure (ALF), LOLA has been shown to prevent brain edema and hepatic encephalopathy which was accompanied by up regulation of muscle glutamine synthase activity and plasma glutamine levels were also raised indicating that LOLA in ALF may be beneficial. 50 A randomized placebo controlled double blind trial of LOLA in patients with ALF was recently published. 51 However LOLA therapy was not associated with decrease in ammonia levels or improvement in encephalopathy or survival (Figure 2).…”
Section: Ammonia Lowering Strategiesmentioning
confidence: 99%
“…An infusion of ornithine-aspartate to rats with ischemic FHF reduced hyperammonemia and prevented the development of brain edema while resulting in a post-translational increase in glutamine synthetase activity in muscle. 22,23 Clinical trials with this agent, commercially available in Europe, should be performed cautiously, because the nitrogenous load could result in worsening of the clinical picture if human muscle does not respond in a similar fashion.…”
Section: The Swollen Astrocytementioning
confidence: 99%